Intercultural Communication of Indonesian-Australian International Special Class Alumni According to Proxemics Dimensions - Melati Mediana Tobing (Ikatan Sarjana Komunikasi Indonesia, 2022)
This article examines the connection between proxemics and cosmopolitanism. Cosmopolitans can be understood as citizens of a borderless state or owners of global citizenship, with their communication also being borderless. Cosmopolitans usually come from many different cultures and use their native languag, but their perception of place is a gradually construced process and built with experience, education or the information they have gathered from media. Indonesian cosmopolitans also have an identity of being global citizens, who like travelling around the world but choose to stay in Indonesia with their family and friends. This article describes about Indonesian cosmopolitans who prefer to live in Indonesia despite the lack of a good living environment. The article also analyzes informant perceptions of space during their time studying in Australia and working in Indonesia. In accordance with the methodology chosen for the study, interviews with three informants of the International Class Program were conducted in Jakarta in July-August 2016. The informants were active students and are currently working near Jakarta. The study identifies the differences inherent in Indonesian cosmopolitans: 1) Indonesian cosmopolitans do not travel but they like living together with their families: “whether or not one eats, what matters is that one is together with family”, and; 2) these new cosmopolitans have an open attitude. This research using a framework of analysis based on proxemics and linked their communication experiences as cosmopolitans after returning to Indonesia as alumni, with several relevant answers based on their nonverbal intercultural communication.